PENGARUH KARAKTERISTIK INDIVIDU DAN PELATIHAN TERHADAP PEMAHAMAHAN SAK ETAP - Rohmawati, Khoirur; Januarti, Indira (Universitas Katolik Indonesia Atma Jaya, 2019)
The use of Financial Accounting Standards Entity without Public Accountability (SAK ETAP) has been launched starting in 2011, although there is still relatively little research on the topic of understanding SAK ETAP. Research on the use of previous SAK ETAP is more inclined to case studies in a particular SME. Cooperatives must make a financial report annually as a form of accountability Board to member. The understanding of accounting employees about SAK ETAP is important because accounting employees are responsible for financial reporting. Therefore, this research needs to be done to know how far the understanding of the accounting section of SAK ETAP.This study aims to analyze the factors that effect on the understanding of the economic enterprise accountants of SAK ETAP. These factors include level of education, educational background, SAK ETAP training, and gender. This study used data obtained from the questionnaire where the respondents were a cooperative accounting officer located in the Pati District. Respondents amounted to 80 who became the sample of the study. The sampling method study was used convenience sampling. The data analysis tool used is multiple regression analysis. The results showed that education level, educational background, and training of SAK ETAP influenced the understanding of SAK ETAP. The higher the level of education, the ability to understand the SAK ETAP is also high. Employees who have an accounting education background were easier to understand SAK ETAP than non accounting education. In addition, SAK ETAP training can also improve employees' ability to understand SAK ETAP. However, gender has no influence in determining the level of understanding of SAK ETAP.